Growth and fillet yield in recirculation systems of Lobotes pacificus (Perciformes: Lobotidae), a species with aquaculture potential - Chacón Guzmán, Jonathan (2019)
The genus Lobotes extends across tropical and subtropical areas of oceans such as the Atlantic and the Pacific; it is extracted in artisanal fisheries, and its aquaculture production technology is still under investigation. The objective of this paper was to evaluate the growth and fillet yield of L. pacificus in recirculated systems. In 2014, for a 100-day period, 132 juveniles were placed in six 10m3 tanks (22 fish/tank), D1 (ranging 5-13 g, x̄ = 8.8 ± 1.9 g, n = 66), and D2 (ranging 14-80 g, x̄ = 44.7 ± 16.4 g, n = 66). Fish were fed to satiety, D1 with artificial feed and D2 with sardines. The weight-length relationship was calculated for each group. Fish had a final weight of 47.7 ± 20.3 g and 612.2 ± 238.7 g in groups D1and D2, respectively, while survival was 98.3% and 72.7% in groups D1 and D2. The whole fish and fillet yields (whole eviscerated fish yield of 89.0 ± 0.5% and fillet yields without skin of 36.1 ± 0.6%) from group D2 were considered acceptable and competitive. The 100 days of culture indicated that L. pacificus reached commercial sizes in less time than other similar fish species; however, the use of sardines as the only source of food was not recommended. This study showed that L. pacificus has high yield potential for aquaculture.